PENGARUH MINAT BELAJAR TERHADAP KEMAMPUAN PRAKTIKUM FISIKA MATERI HUKUM NEWTON PADA MAHASISWA PENDIDIKAN FISIKA - Rizki, Putri Annisa; Rahmadinanti, Moza Oriana; Istifadah, Hanim; Rokhma, Risma Yusliqatur; Kaneishia, Sabrina; Sudarti, Sudarti; Subiki, Subiki (Jurnal Sains Riset, 2023)
This study aims to examine the effect of interest in learning on physics practicum abilities on Newton's Law material in physics education students. The method used is regression analysis with a quantitative descriptive approach. The dependent variable in this study was students' practicum ability, while the independent variable was learning interest as measured by indicators of student interest in practicum, student attention in practicum, and student involvement in practicum. The data used in this study were obtained through primary data collection through questionnaires which were distributed to physics education students who were taking a physics course on Newton's Laws. The research sample consisted of 100 respondents who were randomly selected. The collected data were then analyzed using the regression method to evaluate the effect of the independent variables on the dependent variable. The results of the regression analysis show that simultaneously, the learning interest variable (student interest in practicum, student attention in practicum, and student involvement in practicum) has an effect of 60% on students' practicum ability. This means that 60% of the variation in students' practicum abilities can be explained by the learning interest variable studied, while the remaining 40% is influenced by other factors outside the regression equation. The resulting regression equation is Student Practicum Ability = 53.730 + 0.244 * Student Interest in Practicum + 0.631 * Student Attention in Practicum + 0.588 * Student Involvement in Practicum. However, when individual significance tests were carried out, the p-value for each independent variable (student interest in practicum, student attention in practicum, and student involvement in practicum) was greater than 0.05. Even though interest in learning has a simultaneous effect on the ability of physics practicum on Newton's Law material for physics education students, individually, the variables of interest in learning do not have a significant effect. This shows that there are other factors outside the regression equation that can affect students' practicum abilities. Therefore, further research is needed to identify these factors and dig deeper into the relationship between interest in learning and students' physics practicum abilities.Keywords: Effect of Interest in Learning; Physics Learning; Newton's laws